1983
DOI: 10.1128/iai.40.1.97-102.1983
|View full text |Cite
|
Sign up to set email alerts
|

Generation of hydrogen peroxide by Candida albicans and influence on murine polymorphonuclear leukocyte activity

Abstract: Iodide fixation by murine polymorphonuclear leukocytes (PMN) incubated with viable Candida albicans blastoconidia increases directly with yeast cell concentration up to about 3 x 106 cells per ml, but above this concentration bound activity declines dramatically. To understand the basis for this decline, we examined the oxidative metabolism offungi and stimulated PMN and found some remarkable similarities between these cell types. Both produced 14C02 when incubated with [1-14C]glucose, both reduced cytochrome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…These observations suggest that H 2 O 2producing lactobacilli might play a greater role than H 2 O 2negative lactobacilli in inhibiting C. albicans growth in vivo (11). C. albicans both produces and tolerates low concentrations of H 2 O 2 (24); however, in vitro higher concentrations of H 2 O 2 may be candidicidal (6). Paradoxically, in the same study Hillier et al found no evidence of increased colonization or symptomatic candidiasis in pregnant women completely lacking lactobacilli; hence, the importance of H 2 O 2 requires clarification (11).…”
Section: Discussionmentioning
confidence: 92%
“…These observations suggest that H 2 O 2producing lactobacilli might play a greater role than H 2 O 2negative lactobacilli in inhibiting C. albicans growth in vivo (11). C. albicans both produces and tolerates low concentrations of H 2 O 2 (24); however, in vitro higher concentrations of H 2 O 2 may be candidicidal (6). Paradoxically, in the same study Hillier et al found no evidence of increased colonization or symptomatic candidiasis in pregnant women completely lacking lactobacilli; hence, the importance of H 2 O 2 requires clarification (11).…”
Section: Discussionmentioning
confidence: 92%
“…In this regard, Bistoni et al . [ 41, 42] demonstrated that IL‐4 and IL‐10 inhibited NO‐dependent macrophage killing of Candida albicans and that neutralization of IL‐10 by specific antibodies up‐regulated NO production and protected susceptible mice from infection with Candida albicans . These observations suggest that such anti‐inflammatory cytokines, produced by macrophages through stimulation with yeast cells, may be involved in the inhibition of macrophage NO production by Candida albicans .…”
Section: Discussionmentioning
confidence: 99%
“…For example, Hilger & Danley [ 41] and Danley et al . [ 42] indicated that live Candida albicans suppressed the release of H 2 O 2 by neutrophils, while dead organisms did not. On the other hand, Smail et al .…”
Section: Discussionmentioning
confidence: 99%
“…The mitochondria in C. albicans are capable of generating extracellularly released ROS [5]. In our previous work we demonstrated that ROS generation by C. albicans is dependent on morphogenesis and that their highest levels are found in cells with hyphal form [6].…”
Section: Introductionmentioning
confidence: 92%